Recommendations for development and implementation of the professional modelcompetences in the sphere of training of specialists for of the national cyber-security system - Бурячок, Володимир Леонідович; Богуш, Володимир Михайлович (Ukrainian Information Security Research Journal, 2018)
The article analyzes the process of formation of information and cyberspace, and as a result, a conclusion is made about the intensification of information confrontation between countries and their entry into a qualitatively new phase of mutual relations - information and cybernetic confrontation. This requires a quali-tatively new approach to the training of IT professionals, with its orientation primarily on the practical plane in the field of information and cyber-non-security. To solve this problem, the article identifies the most priority key directions for the training of such specialists. Based on the results of the analysis of Ukrainian legislation on cybersecurity and the standard NATO training curriculum on cybersecuri-ty, a model for training specialists for the national cybersecurity system was proposed. The competence and learning out-comes implemented in the model can be used as a basis for the development of educational programs and curricula for qualitative training of specialists for the national cybersecurity system, namely bachelors of cybersecurity, as agreed by the National Agency for Quality Assurance in Higher Education in 2017, new standards on cybersecurity at the following edu-cational-professional and educational-scientific levels. In the article several basic classes of the model of professional com-petencies in the field of training specialists for the national cybersecurity system were proposed. Given that the main sub-jects of the national cybersecurity system in accordance with the Constitution and laws of Ukraine is the State Service for Special Communications and Information Protection of Ukraine, the National Police Ukraine, the Security Service of Ukraine, the Ministry of Defense of Ukraine and the General Staff of the Armed Forces of Ukraine, intelligence bodies and the National Bank of Ukraine, the work agreed upon with the tasks assigned to these structures, models of professional competencies for the preparation of their personal cooperation.